Sport specific adaptation in resting length of pectoralis minor in professional male golfers - Mackenzie, T. A.; Herrington, L.; Funk, L.; Horlsey, I.; Cools, A. (Journal of Athletic Enhancement, 2015)
Objective: In professional male golfers the shoulder is the third most commonly injured area with the lead/non-dominant shoulder three times more likely to be injured than the trail/dominant shoulder. Resting length of pectoralis minor musculature influences scapular and glenohumeral orientation which when suboptimal is associated with shoulder injuries. This study investigates the resting pectoralis minor muscle length in professional male golfers. Method: Forty five male golfers on European Challenge Tour and thirty six control volunteers met the inclusion criteria for the study. Resting pectoralis minor length was measured in the supine position with the Palmmeter device. Results: Within groups: controls exhibited a significantly longer pectoralis minor muscle on the non-dominant side (p=0.01), and golfers had a significantly longer pectoralis minor muscle on the trail/dominant side (p=0.01). Between groups: controls exhibited a significantly longer pectoralis minor length on the non-dominant/ lead side when compared to golfers (p=0.01). Conclusion: When compared to age-matched controls professional male golfers have a unique pattern of resting pectorals minor muscle length, with longer pectoralis minor length noted in the trail/ dominant shoulder. Comparison of the lead/non-dominant shoulder with controls highlights that golfers have a shorter pectoralis minor length which in turn affects scapular and glenohumeral orientation. This may place the golfer at greater risk of shoulder injury in the lead side.